Application of Discovery Learning Model in Increasing Student Interest and Learning Outcomes - Yusrizal Yusrizal; Mustafa Mustafa; Susanna Susanna; Rosnidar Rosnidar (Postgraduate, University of Mataram, 2021)
This research aims to find out the application of discovery learning models in increasing students' interest and learning outcomes in harmonic vibrational materials in MAN 4 Aceh Besar. The method in this study is quasi-experimentation with the design of a pretest-posttest control group. The instruments used are questionnaires and problems. The results showed that the average N-gain of student learning interest in the experimental class was 0.79 high category and control class 0.28 low category. The results of each experimental class indicator included a very positive category while the category control class was positive. Based on the results of the analysis of both classes, it can be concluded that the average interest in student learning in the experimental class is more increased than in the control class, especially on indicators of student engagement. The average N-gain result of student learning outcomes in the experimental class obtained a score of 0.61 moderate categories, then in the control class obtained a score of 0.35 medium category. Based on the test results, the average of the two classes obtained significance scores of 0.000 < 0.05, meaning that there was a difference in the average learning outcome of students in experimental classes and control classes. This proves that the discovery learning model's application can improve students' learning outcomes higher than the discovery learning model in the control class. This study concludes that the application of discovery learning models can increase students' interest and learning outcomes in harmonic vibrational materials in MAN 4 Aceh Besar